(untitled) (Journal of Pathology of Nepal, 2016)
Background: Carcinoma of breast has become the major public health problem among females in developing as well as developed countries. InNepal it comprises 6% of total cancers cases and often diagnosed at advanced stage. Surgical removal or modified radical mastectomy (MRM) is the most commonly used tools for disease management. The objective of this study is to identify the clinical, macroscopic and microscopic features of MRM specimens. Materials and methods: This prospective cross-sectional study was carried out at Department of Pathology, Bhaktapur Cancer Hospital, Bhaktapur, Nepal. Macroscopic and microscopic examination provided the tumor size, stage, grade, lymph node status, lympho-vascular invasion and perineural invasion. Data were collected and analyzed using SPSS 16. Results: The study comprised 112 breast cancer patients of which 109 (97.3%) were females and 3 (2.7%) were males. Invasive ductal carcinoma no specific type was the most common type of breast carcinoma. (84 cases) accounting 75% of total cases. Carcinoma with medullary features was second most common (6 cases) comprising 5.4% cases followed by lobular, papillary, apocrine, mucinious and NST mixed types. Grade II tumors were most frequent grade observed in 76.79% cases followed by Grade I (12.50%) and Grade III (10.71%). Conclusion: As a conclusion invasive ductal carcinoma was the most common histological type breast cancer and the tumors were found at T2 and N3 stage i.e maximum at grade II. Our study provides prognostic significance of histo-pathological information in breast cancer management.